2011
DOI: 10.3797/scipharm.1107-02
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Evaluation of Dibenzo[b,e]oxepin-11(6H)-one O-Benzoyloxime Derivatives

Abstract: A series of dibenzo[b,e]ox(thi)epin-11(6H)-one O-benzoyloximes has been synthesized and structurally elucidated by means of IR, 1H-NMR, 13C-NMR, MS, and elemental analysis. The newly developed compounds were screened at concentrations of 200–25 μg/mL for their antibacterial activity against Gram+ve organisms such as Methicillin-Resistant Staphylococcus Aureus (MRSA), Gram−ve organisms such as Escherichia coli (E. coli), and at the same concentration range for their antifungal activity against fungal strain Asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Current synthesis methods involve several reaction steps or restrictive reaction conditions such as strongly acidic media (intramolecular Friedel-Crafts) which preclude the incorporation of reactive functional groups. 5,8,9 Based primarily on work directed toward the preparation of symmetrical dibenzosuberones via intramolecular Parham cyclizations described by Reames et al 10 We have found that the Parham protocol is well-suited for the preparation of a variety of these classes of compounds. 11 This Letter describes a general protocol for a straightforward synthesis of diaryl-fused seven-membered heterocyclic ketones under Parham conditions.…”
Section: Introduction and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current synthesis methods involve several reaction steps or restrictive reaction conditions such as strongly acidic media (intramolecular Friedel-Crafts) which preclude the incorporation of reactive functional groups. 5,8,9 Based primarily on work directed toward the preparation of symmetrical dibenzosuberones via intramolecular Parham cyclizations described by Reames et al 10 We have found that the Parham protocol is well-suited for the preparation of a variety of these classes of compounds. 11 This Letter describes a general protocol for a straightforward synthesis of diaryl-fused seven-membered heterocyclic ketones under Parham conditions.…”
Section: Introduction and Discussionmentioning
confidence: 99%
“…The benzo-fused seven-membered heterocyclic ketones have been shown to possess central nervous system pharmacological activity while products derived from diaryl-fused 6,7,6 heterocyclic compounds have been shown to have utility in a variety of different therapeutic applications including treatment of cognitive disorders such as Alzheimer's disease and Huntington's disease through inhibition of histone deactylase, 1 the treatment of sleep disorders, [2][3][4] antimicrobial agents, 5 and agonists of the peroxisome proliferator-activated receptor 6 to name a few (Fig. 1).…”
Section: Introduction and Discussionmentioning
confidence: 99%
“…For several years now, the pharmaceutical and chemical industries have shown great interest in the development of new oxepine derivatives for therapeutic purposes. [1][2][3][4] In this sense, a report showed the preparation of benzoxepine-1,2,3-triazol via reaction of an azide analog with a terminal-alkyne derivative. [5] In addition, other data showed the synthesis of an oxazepine-dione analog from a semicarbazone.…”
Section: Introductionmentioning
confidence: 99%
“…Isobenzofuranone derivatives are an important class of compounds displaying a variety of biological effects, such as antioxidant, antimicrobial, antiplatelet, cytotoxic activity and antiarrhythmic effects [ 1 , 2 , 3 , 4 ]. As sources of bioactive substance, fungi are now considered as efficient producers of biologically active and chemically novel compounds.…”
Section: Introductionmentioning
confidence: 99%